Du prêtre au traître : destins croisés du prélat par Mongo Beti et Ramon J. Sender - Ebé Mathurin Ovono (Multilinguales)
This contribution aims at crossing the behavior of the Church during the French colonization in Africa and during the Civil War in Spain, through Le Pauvre Christ de Bomba (1956) by Mongo Beti and Réquiem por un campesino español (1960) by Ramón J. Sender. The points of comparison are essentially the theme of the religion around the character of the priest, the posture of the narrator embodied by the boy of mass and the paratext with a priority granted to the titles. We conclude on the relevance of the question posed by these two novels and which is still debate, namely the separation of Church and State.